Reframing EFL Pedagogy via Student Voices: A Reflexive Thematic Study of Non-Cognitive Dimension - Jhoni Eppendi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Learner autonomy and engagement are central to English as a Foreign Language (EFL) instruction. However, relational, emotional, and pedagogical factors shaping students’ experiences remain underexplored in Southeast Asian higher education. This study investigates how second-year undergraduate EFL learners experience and interpret emotionally responsive, participatory, and relationally grounded teaching practices, and how these practices shape learners’ engagement, psychological safety, and agency in English learning. Methodology: A qualitative approach was employed with 95 law undergraduate students in a compulsory English course at Universitas Borneo Tarakan. Data were collected through reflective journals, interviews, and classroom observations. Reflexive thematic analysis explored how learners experienced and interpreted emotionally responsive, participatory, and relationally grounded teaching practices. Findings: Six interrelated pedagogical dimensions emerged: Voice, Simplicity, Experience, Upliftment, Objectivity, and Accessibility. Across all dimensions, the lecturer’s consistent reinforcement of expectations, encouragement, and responsiveness was pivotal, fostering trust, predictability, and psychological safety. This consistency empowered students to engage confidently, take ownership of their learning, and experience a fair and inclusive classroom. Novel concepts such as pedagogical upliftment, instructional simplicity, and relational accessibility capture the affective and relational qualities of teaching most valued by learners. Conclusion: Non-cognitive dimensions, enacted through consistent pedagogical practice, are foundational to effective EFL instruction. Pedagogical consistency reinforces emotional presence, learner agency, and relational trust, creating classrooms where students feel safe, supported, and actively engaged. Originality: The study offers a student-informed, empirically grounded framework of non-cognitive EFL pedagogy, bridging theory and practice. By articulating six instructional dimensions and highlighting the role of pedagogical consistency, it addresses a critical gap in Southeast Asian higher education, providing actionable insights for inclusive, humanizing, and context-responsive teaching.